United States. Senate. Committee on the Judiciary. Subcommittee to Investigate Individuals Representing the Interests of Foreign Governments records - United States. Congress. Senate. Committee on the Judiciary. Subcommittee to Investigate Individuals Representing the Interests of Foreign Governments
Depositions and testimony of hearings held by the Subcommittee to Investigate the Activities of Individuals Representing the Interests of Foreign Governments relating to transactions between Billy Carter, brother of President Jimmy Carter, and his business dealings with Libya. Includes depositions by Billy Carter, Lloyd N. Cutler, Hamilton Jordan, Bert Lance, Hamilton Jordan, and Jody Powell.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Carter, Billy; Carter, Jimmy, -- 1924-; Cutler, Lloyd N; Jordan, Hamilton; Lance, Bert, -- 1931-2013.; Powell, Jody, -- 1943-2009.; Foreign agents -- United States; Libya -- Foreign relations -- United States; United States -- Foreign relations -- Libya